Towards an Interreligious Ecotheological Leadership Paradigm to Overcome the Ecological Crisis - Aluysius Budi Purnomo (P3TK, Sanata Dharma University, 2020)
An increasingly complex ecological crisis due to misperceptions, wrong perspective and behaviour in managing the environment requires an interreligious ecotheological leadership paradigm to evaluate and change it. However, there is no conceptualization of such leadership. This paper elaborates my personal praxis in involving to maintain the integrity of creation and the environment preservation to construct a paradigm of an interreligious ecotheological leadership in overcoming the ecological crisis. The praxis with the interreligious activists in three places namely Kendeng, Gedongsongo and Tambakrejo (Central Java) became a starting point of this reflection. Starting with an overview of environmental problems, an interreligious ecotheological praxis is performed. Then, I propose the interreligious ecotheological leadership as a new paradigm to evaluate misperception, wrong perspective and behaviour in order to overcoming ecological crisis. I also offer the six characteristics of an interreligious ecotheological leader based on my interreligious ecotheological praxis and some purposive literature. All is discussed and reflected in the lens of the interreligious ecotheology as a part of contextual theology based on the personal praxis supported by the available literature and the Catholic Social Teaching, especially the Laudato Si.DOI:doi.org/10.24071/jaot.2020.020102